LEGAL PROTECTION OF BRANDS AND RISK OF FORGING PRODUCTS THAT ARE FACED BY SMALL AND MEDIUM ENTERPRISES (UKM) (International Journal of Psychosocial Rehabilitation, 2020)
Small and Medium Enterprises (SMEs) are very vulnerable to the threat of counterfeiting and unlicensed use of Trademarks as is the case with other large companies. Generally the obstacles that occur especially for SMEs are limited understanding of the function of the brand and its impact in the event of counterfeiting. Brand violations generally occur when business competition is felt so high in the Product sector. This study aims to determine what legal efforts can be given to be able to protect against the brand and how to strengthen the brand itself. The method in this research is normative juridical and interviews with four SME business people. The results show that legal protection can be done by (1) Providing an understanding of the UKM itself, (2) Managing and fostering the UKM, (3) Registering either independently or collectively.